PENGARUH WANITA DALAM KETAHANAN EKONOMI KELUARGA - Fathul Aminudin Aziz; Akhris Fuadatis Solikha; Irvan Ashari (Jurnal Penelitian Agama, 2017)
Abstract: The purpose of this study is to examine the influence of age, education, the sum of children, work time, and experience on women who became plaited mat of pandan toward family income. This study conduct simple random sampling and estimate population with Slovin formulate. The data analysis technique in this study are descriptive analysis, classical assumption test, multiple regression analysis, hypothesis test uses F test, and t test. The result showed that variable of work time is giving positive significant influence on family income but variable age, education, the sum of children, and experience does not giving significant influence on family income. Keywords: age, education, the sum of children, work time, experience, and family income.